Cost variation analysis of ACE inhibitors in India - Wadagbalkar, Prashant; Patel, Poonam; Raipurkar, Swati V. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Cardiovascular diseases are the most prevalent cause of death and disability in developed and developing countries. There is a wide variation in the prices of antihypertensive drugs marketed in India. Thus, a study was planned to find out variation in cost in the ACE Inhibitors available in India either as a single drug or in combination and to evaluate the difference in cost of various brands of the same ACE Inhibitors and ARBs by calculating percentage variation in cost in Indian rupees. Methods: Minimum and maximum costs in rupees (INR) of antihypertensive agents manufactured by different companies, in the same strength and dosage forms were obtained from “current index of medical specialties” January April 2016 and Drug Today October-December 2016. The cost ratio and percentage cost variation were calculated for each generic antihypertensive agent (ACE Inhibitors and ARBs). Results: This study shows that there is a wide variation in the prices of different brands of same ACE Inhibitors and ARBs in Indian market. Highest cost variation 400% is for Lisinopril (2.5mg), followed by Enalapril (10mg) 394.16%, Telmisartan (20mg) 322.22%. Conclusions: There is a wide difference in the cost of different brands of ACE Inhibitors and ARBs available in India. They have important role in management of hypertension particularly if associated with other morbidities like diabetes. The clinicians prescribing these drugs should be aware of these variations in cost so as to reduce the cost of drug therapy and increase the patient adherence to the therapy.